Bioactivity assessment of peptides derived from salted jellyfish (Rhopilema hispidum) byproducts - Pratchaya Muangrod; Wiriya Charoenchokpanich; Sittiruk Roytrakul; Vilai Rungsardthong; Sawanya Charoenlappanit; Benjamaporn Wonganu; Lueacha Tabtimmai; Phumin Chamsodsai; Federico Casanova; Benjawan Thumthanaruk (PLoS ONE, 2025)
The identification of multifunctional peptides derived from marine byproducts represents a significant challenge in the field. In Thailand, the fisheries industry exports salted jellyfish, which results in low-value byproducts primarily employed for animal feed. Previous studies have indicated the bioactivities of jellyfish protein hydrolysates from Lobonema smitthii; however, the multifunctional properties of Rhopilema hispidum remain largely unexplored. This research aimed to characterize synthetic bioactive peptides sourced from the byproducts of salted jellyfish (R. hispidum), with a specific emphasis on their antioxidant, angiotensin-I-converting enzyme (ACE) inhibitory, and anti-inflammatory activities. The hydrolysate obtained from the umbrella portion, subjected to pepsin treatment at a 3:20 enzyme-to-substrate ratio for 48 h at 37 °C, demonstrated the highest levels of antioxidant activity (DPPH =  1.85 ± 0.05 mM TE/mg protein, ABTS =  7.28 ± 0.03 mM TE/mg protein, FRAP =  3.04 ± 0.12 mM FeSO4/mg protein). Following purification, 18 novel peptides exhibiting high antioxidant scores (FRS+CHEL >  0.48) were identified and synthesized. Notably, the peptide MVVACVLPEA exhibited significant antioxidant (DPPH =  56.07 mM TE/mg protein), ACE inhibitory (91.69%), and anti-inflammatory activities (NO release =  34.59 µ M) without cytotoxic effects, although it is important to note that two other peptides did demonstrate cytotoxicity. This investigation reports a total of 16 synthesized peptides that possess triple functional activities—antioxidant, ACE inhibitory, and anti-inflammatory—without cytotoxicity, thus highlighting their potential applications in health-related fields.